Diversity and floral composition changes in intensively cultivated practical year training program farm of the university of Ibadan, Nigeria (2018)
Higher Institutions where agriculture is taught are required by National University Commission to have large areas of land for practical and demonstration activities. The lands are often cultivated intensively for decades under the same soil management practices, thus making them to become invaded with weeds which overtime become adapted to the ecosystem at the expense of soil productivity. The study was conducted to determine the species composition, invasiveness, spatial distribution of weed species and diversity of weeds on the site for Practical Year Training Programme (PYTP) of the Faculty of Agriculture, University of Ibadan in two consecutive years. The PYTP farm was floristically surveyed by using 21 plots of 150 m2 each and a strip of 5 m round was maintained for edge effects. Six (1 m2) square quadrats (126 in all) were randomly laid on each plot to enumerate the herbaceous flora of the farm. Flora composition, frequency and density values were evaluated for Relative Importance Values (RIV, %) following standard procedures. Soil of the farm was routinely analysed for its adequacy for agricultural purposes. A total of fifty two (52) plant species in seventeen (17) families were enumerated in the first year while a total of thirty (30) plant species belonging to fourteen (14) families were enumerated in the second year. In the first year, Tridax procumbens had the highest Relative Importance Value (11.73), distantly followed by Cynodon dactylon (6.44). Tridax procumbens was prevalent in plots not subjected to crop rotation. The abundance of plants was low on clay soils. Margalef index (12.81), Mehinick index (6.959), and Dominance (0.05262) indicated high overall species diversity, high species diversity in each plot, and low overall dominance respectively. In the second year, Gomphrena celosioides had the highest RIV (18.66) followed by Panicum maximum (12.43). Three soil types (sandy loam, loamy sand and clay) were identified. The soils were acidic (pH 4.7 – 4.8). Sandy loam and loamy sand soils had comparatively higher organic matter content than clay soil. The nitrogen concentration of the soils was generally low (0.6-1.33 g/kg). The Practical Year Training Programme land of the University of Ibadan is not productive and therefore should be allowed to rest for a long period of time. Conservation agricultural practices are recommended for the land anytime it is to be cultivated to deter further degradation.